The role of Northern Hemisphere summer insolation for millennial-scale climate variability during the penultimate glacial - Fohlmeister, Jens; Luetscher, Marc; Spötl, Christoph; Schröder-Ritzrau, Andrea; Schröder, Birgit; Frank, Norbert; Eichstädter, René; Trüssel, Martin; Skiba, Vanessa; Boers, Niklas (Communications earth & environment, 2023)
Previous glacial intervals were punctuated by abrupt climate transitions between cold (stadial) and warm (interstadial) conditions. Many mechanisms leading to stadial-interstadial variability have been hypothesized with ice volume being a commonly involved element. Here, we test to which extent insolation modulated stadial-interstadial oscillations occurred during the penultimate glacial. We present a replicated and precisely dated speleothem record covering the period between 200 and 130 ka before present from caves located in the European Alps known to be sensitive to millennial-scale variability. We show that the widely proposed relationship between sea level change and stadial-interstadial variability was additionally modulated by solar insolation during this time interval. We find that interstadials occurred preferentially near maxima of Northern Hemisphere summer insolation, even when sea level remained close to its minimum during peak glacial periods. We confirm these observations with model simulations that accurately reproduce the frequency and duration of interstadials for given sea-level and insolation forcing. Our results imply that summer insolation played an important role in modulating the occurrence of stadial-interstadial oscillations and highlight the relevance of insolation in triggering abrupt climate changes.
Gesehen am 03.08.2023